1998
DOI: 10.1128/jvi.72.1.330-338.1998
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Secreting Cell Responses and Protective Immunity Assessed in Gnotobiotic Pigs Inoculated Orally or Intramuscularly with Inactivated Human Rotavirus

Abstract: Newborn gnotobiotic pigs were inoculated twice perorally (p.o.) (group 1) or intramuscularly (i.m.) (group 2) or three times i.m. (group 3) with inactivated Wa strain human rotavirus and challenged with virulent Wa human rotavirus 20 to 24 days later. To assess correlates of protection, antibody-secreting cells (ASC) were enumerated in intestinal and systemic lymphoid tissues from pigs in each group at selected postinoculation days (PID) or postchallenge days. Few virus-specific ASC were detected in any tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 41 publications
3
55
0
9
Order By: Relevance
“…As a constant in our results, the number of IgG ASC in gut associated tissues was higher than the number of IgA ASC. This fact has also been described in previous reports (Van Cott et al, 1993;Yuan et al, 1996Yuan et al, , 1998 studying immunity by ELISPOT in TGEV and rotavirus infections. Even though there is no clear explanation for this fact, the possibility of extraintestinal stimulation of the immune system has been proposed.…”
Section: Discussionsupporting
confidence: 85%
“…As a constant in our results, the number of IgG ASC in gut associated tissues was higher than the number of IgA ASC. This fact has also been described in previous reports (Van Cott et al, 1993;Yuan et al, 1996Yuan et al, , 1998 studying immunity by ELISPOT in TGEV and rotavirus infections. Even though there is no clear explanation for this fact, the possibility of extraintestinal stimulation of the immune system has been proposed.…”
Section: Discussionsupporting
confidence: 85%
“…A lack of understanding of mechanisms to induce intestinal immunity and the correlates of protective immunity in neonates has impaired development of safe and effective vaccines against enteric viruses for farm animals and children. Protection induced by candidate vaccines observed in studies using lab animals, such as mouse and rabbit models of rotavirus subclinical infections often do not predict the protective ef®cacy of these vaccines against clinical infections in studies of neonatal large animals O'Neal et al, 1998;McNeal et al, 1999a,b;Yuan et al, 1998Yuan et al, , 2000Welter and Welter, 1990). Efforts to identify immunologic correlates of protective immunity to rotavirus infection using knockout mice for selected immune-related genes, passive lymphocyte transfer experiments, and immunodepletion of selected populations of lymphocytes by the injection of speci®c monoclonal antibodies have shown that none of the known effectors for acquired immune responses (CD4 or CD8 T-cells, antibodies, interferon-g, perforin, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite the numerous trials and decades of research, effective vaccines are still not available for these or other viral agents that cause gastroenteritis. Although, research efforts have appeared promising, vaccine field trials continue to produce inadequate results or fail entirely (de Leeuw et al, 1980;Myers and Snodgrass, 1982;Snodgrass et al, 1982;Waltner-Toews et al, 1985;Yuan et al, 1998). The inadequacy of rotavirus vaccines may be explained, in part, by the complex antigenic diversity of the group A rotaviruses (Woode et al, , 1987Zheng et al, 1989;Hardy et al, 1991;Parwani et al, 1993;, and by doubts concerning which of the two main antigens, VP4 or VP7, is the most important antigen to induce immune protection (Ward et al, 1993;.…”
Section: Introductionmentioning
confidence: 99%